1991
DOI: 10.1063/1.348536
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of a high irradiance, subpicosecond laser pulse with aluminum: The effects of the prepulse on x-ray production

Abstract: The conversion efficiency into kilovolt line radiation for 248-nm light at 1017 W/cm2 on an aluminum target is measured. The x-ray yield is found to increase with the scale length of the target plasma. The interaction is modeled as resonance absorption, and the plasma scale length is determined from the prelase energy and irradiance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…This is close to the known damage threshold of aluminum. We note that our ASE pedestal intensity was smaHer, by more than one order of magnitude, than the one used in a similar study by Cobble and co-workers [45] who used 650 fs, 248 nm laser pulses. No evidence was found for a variation of the absorbed laser energy with the polarization state of the laser.…”
Section: Methodsmentioning
confidence: 84%
See 3 more Smart Citations
“…This is close to the known damage threshold of aluminum. We note that our ASE pedestal intensity was smaHer, by more than one order of magnitude, than the one used in a similar study by Cobble and co-workers [45] who used 650 fs, 248 nm laser pulses. No evidence was found for a variation of the absorbed laser energy with the polarization state of the laser.…”
Section: Methodsmentioning
confidence: 84%
“…An ultrafast shutter consisting of a self-phase modulation water ceH and a diffraction grating was added in front of the photodiode to reduce the short pulse intensity in the clear aperture of the diode thus avoiding high voltage distortions in the diodeoscilloscope combination. The delay of the onset of the prepulse with respect to the main pulse and the prepulse energy can be varied [45] by modifying the operating conditions of the Nd:YAG pump laser. Maximum x-ray conversion, monitored by a filtered {hv) 1 keV) x-ray photodiode, was reached for an ASE fluence of 0.7 J/cm [43].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basic studies of femtosecond laser pulse interaction with aluminium have previously been reported [6][7][8]. The importance of a laser prepulse in increasing the XUV and X-ray yields is well known and has, to some extent, already been studied in the sub-picosecond region [4,[9][10][11][12][13][14]. The aim of this work was to study the possibility of generating coherent X-rays from high-intensity, ultra-short laser pulses.…”
mentioning
confidence: 99%